INFLUENCE OF GROWING TECHNOLOGIES OF HEMPS ON THE NOURISHING STATE OF SOIL - Пісковий, М. Б.; Магда, М. А.; Пилипченко, А. В.; Ситник, В. П. (Scientific Progress & Innovations, 2017)
The article presents the results of research on the effectiveness of hemp cultivation in the conditions of classical technology and organic farming. It has been determined how the technology of hemp cultivation influences the change of the biological state of the soil, the yield of seeds and stems, as well as the study of ways to ensure the culture of hemp with nutritional elements. The research has established that the cultivation of hemp straw in the conditions of organic production does not contribute to increasing the yield of seeds, compared with the transition from classical to biological technology (intensive). The accumulation and transformation of fresh organic matter of the hemp plant residues depends on the components of the organic farming technology, which enable the microflora of the soil to not tolerate stress from the effects of fertilizer and plant protection products.